2016
DOI: 10.21767/2254-6081.100055
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Hypofractionated Radiation in Carcinoma Breast

Abstract: Aim: Comparison of two different radiation fractionation schedules is done in post mastectomy breast cancer cases in relation to loco regional control, acute and late toxicities, survival and overall treatment time (O.T.T). The patient, tumor and treatment related parameters have also been studied. Materials and Methods:Between December 2011 and December 2013, hundred patients of stage II to III carcinoma breast treated with surgery and chemotherapy received adjuvant radiation therapy with two different fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Kouloulias et al, (2016) reported grade 2-3 dermatitis at 29%, while Ko et al, (2015) reported grade 2 at 10.7% in HFRT. The present study found grade 2 at 42.2% in CFRT which is comparable to the results from Rastogi et al, (2018) and Alam et al, (2016). Cardiotoxicity is a late complication which significantly occurs in patients who receive left-sided radiotherapy (Sardar et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Kouloulias et al, (2016) reported grade 2-3 dermatitis at 29%, while Ko et al, (2015) reported grade 2 at 10.7% in HFRT. The present study found grade 2 at 42.2% in CFRT which is comparable to the results from Rastogi et al, (2018) and Alam et al, (2016). Cardiotoxicity is a late complication which significantly occurs in patients who receive left-sided radiotherapy (Sardar et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Rastogi et al, (2018) found grade 2 acute dermatitis 40% in CFRT and 42% in HFRT. Similarly, by Alam et al, (2016) that grade 2 were seen at 42% in CFRT and 54% in HFRT. Kouloulias et al, (2016) reported grade 2-3 dermatitis at 29%, while Ko et al, (2015) reported grade 2 at 10.7% in HFRT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 38 Additionally, a number of retrospective studies have reported that patients who received HF-PMRT experienced significantly lower or similar rates of acute skin toxicity compared with those who received SF-PMRT. 32 , 33 , 34 , 36 , 40 , 41 …”
Section: Methodsmentioning
confidence: 99%
“…31 Because shorter treatment regimens are more convenient and cost-effective, there is growing interest globally in applying hypofractionated treatments to patients requiring PMRT and/or RNI (Table 1). [32][33][34][35][36][37] The largest phase III trial to date comparing hypofractionated versus conventional PMRT was conducted in China. 36 More than 800 patients treated with mastectomy without reconstruction were randomly assigned to conventional (50 Gy in 25 fractions) or hypofractionated (43.5 Gy in 15 fractions) radiation to the chest wall, level III axillary nodes, and supraclavicular nodes, without treatment of IMNs.…”
Section: Survival and Pmrtmentioning
confidence: 99%